ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN STUDY PADA FOTOCOPY LANCAR BARU SEMARANG - Setyawan, Aditya; Rizkiana, Citra; Widyakto, adhi (Fakultas Ekonomi, Universitas Semarang, 2022)
This study aims to examine the Analysis of the Effect of Price Perception, Service Quality and Product Quality on Customer Satisfaction (study on a new copy of the new Semarang). The population of this research is the consumers of the Semarang New Current Photocopy. The sample used in this study were 96 respondents. In this research, purposive sampling, which is a sampling technique that provides the opportunity to become a member of the sample with certain criteria. Then the method of data collection through questionnaires and data analysis using SPSS 21 which includes validity, reliability, classical assumption test, multiple regression analysis, hypothesis testing using t test and R2 test. The results of this study indicate that all independent variables, namely price perception (X1), service quality (X2), and product quality (X3) have a positive and significant effect on customer satisfaction (Y) partially or simultaneously (together). . Based on the coefficient of determination of 0.798, which means that 79.8 percent of the customer satisfaction variable can be explained by the price perception variable, service quality and product quality while the remaining 20.2 percent is explained by other variables outside of this study.